REFUNGSIONALISASI KELEMBAGAAN KECAMATAN DALAM KOORDINASI BIDANG KESEHATAN DI KECAMATAN MARPOYAN DAMAI TAHUN 2016 - Alfindi Rahman; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
A change of centralized and decentralized governance system, marked by the issuance of law 23 of 2014 on regional governance. The change can be seen from the shift of status and position of an institution in the whole formation of local government system. Mayor of Pekanbaru as one of the municipal governments in Indonesia is not spared from the consequences, the problem until now delegation of some authorities that have been delegated to the sub district although it has been established according to the delegation of authority regulated in mayoral regulation Pekanbaru number 11 of 2013 about delegation of some authority of mayor Pekanbaru to sub to organize regional government affairs covering 8 aspects. But the delegation of authority to the subdistrict chief, especially the marpoyan subdistrict, is still not running optimally as a regional tool, especially in the aspect of coordination in the field of health.The implementation of the delegation of government authority in the field of health from the mayor of Pekanbaru to the marpoyan subdistrict peace is not running optimally. First, the system. The lack of coordination meetings with the regional apparatus unit made the coordination of the subdistrict heads with the regional apparatus working unit still less intertwined. Second, human resources. Camat is not fully able to perform its duties on the grounds of lack of human resources and existing training is less support the empowerment of existing human resources. Third, the relavant institutions. Clash of coordination done by subdistrict head with unit of work of regional device that is in division of duty, but it still not done.Keywords: Refunctionalization, sub district institutions, coordination, delegation of authority